Advocacy for youth mental health in Europe: a policy analysis - Gonçalves, M. (2014)
Background: According to both the WHO Europe and the European Commission, youth mental health is a key area of concern in Europe. Fifty-two European countries signed a declaration and action plan for mental health at the Helsinki Conference in January 2005, with youth mental health a top priority. Methods: This paper reviews the theory, research, and practice on the topic in the WHO European Region and presents important implications for policy, research, and practice. It states problems related to youth mental health and then discusses different ways of solving them with policy. Results: Mental illness, especially emotional and conduct problems, as well as learning disabilities, is growing among European children and adolescents. However, stigma continues to be a significant barrier to effective promotion of youth mental health. Stigma can be related to others' perceptions of youth with mental distress, perceptions of mental health workers, perceptions of mental health treatment, and perceptions of mental health/illness itself. Conclusion: Advocacy to reduce stigma in health service settings, schools, and policy arenas can be an effective means by which to effect cultural change regarding mental health issues.